Peningkatan Motivasi Belajar Mata Pelajaran Bahasa Siswa melalui Model Team Game Tournamen Berbasis Media Quizizz - Yusnaeni; Rahalaka, Maria Kristina P. (Universitas Tidar, 2025)
This classroom action research was conducted to examine the extent to which the application of the Team Game Tournament (TGT) model combined with the Quizizz game media can increase students' learning motivation. The subjects of this study were 30 students of class XII I of SMAN 5 Kupang. This research was carried out in two cycles, each cycle consisting of stages of planning, implementation, observation and reflection. The data measured were the activeness and learning motivation of students. The activeness of students was measured using an observation sheet of learning implementation observed by two observers, while learning motivation was measured using a motivation questionnaire consisting of 20 items. The indicators measured in the motivation questionnaire consisted of attention, relevance, satisfaction, and confidence. The data were analyzed descriptively. The results of the study obtained: 1) in cycle I, students were seen to be inactive, lacking initiative in noting down important points about the material, and in cycle II they were seen to be active and enthusiastic in answering questions from teachers and friends, and were brave enough to ask questions. 2) students' learning motivation increased, in cycle I 60% were very good: 6.66 were quite good: and 33% were not good. While in cycle II, 90% of students were categorized as very good, and 10% were quite good. The results of this study indicate that the use of the TGT model based on Quizizz media can increase students' learning activity and motivation.